Prion protein (PrP) gene-knockout cell lines: insight into functions of the PrP - Sakudo, Akikazu; Onodera, Takashi (Frontiers in Cell and Developmental Biology, 2015)
Elucidation of prion protein (PrP) functions is crucial to fully understand prion diseases. A major approach to studying PrP functions is the use of PrP gene-knockout (Prnp-/-) mice. So far, six types of Prnp-/- mice have been generated, demonstrating the promiscuous functions of PrP. Recently, other PrP family members, such as Doppel and Shadoo, have been found. However, information obtained from comparative studies of structural and functional analyses of these PrP family proteins do not fully reveal PrP functions. Recently, varieties of Prnp-/- cell lines established from Prnp-/- mice have contributed to the analysis of PrP functions. In this mini-review, we focus on Prnp-/- cell lines and summarize currently available Prnp-/- cell lines and their characterizations. In addition, we introduce the recent advances in the methodology of cell line generation with knockout or knockdown of the PrP gene. We also discuss how these cell lines have provided valuable insights into PrP functions and show future perspectives.